Forecasting stock market (realized) volatility in the United Kingdom: Is there a role of inequality?. (27th September 2020) - Hassani, Hossein; Yeganegi, Mohammad Reza; Gupta, Rangan; Demirer, Riza
Abstract: In this paper, we analyze the potential role of growth in inequality for forecasting realized volatility of the stock market of the UK. In our forecasting exercise, we use linear and nonlinear models as well as measures of absolute and relative consumption and income inequalities at quarterly frequency over the period of 1975 to 2016. Our results indicate that, while linear models incorporating the information of growth in inequality does produce lower forecast errors, these models do not necessarily outperform the univariate linear and nonlinear models based on formal statistical forecast comparison tests, especially in short‐ to medium runs. However, at a one‐year‐ahead horizon, absolute measure of consumption inequality results in significant statistical gains for stock market volatility predictions – possibly due to consumption inequality translating into both political and social uncertainty in the long run.